2009
DOI: 10.3892/or_00000583
|View full text |Cite
|
Sign up to set email alerts
|

The level of fasting serum insulin, but not adiponectin, is associated with the prognosis of early stage hepatocellular carcinoma

Abstract: Abstract. Impaired glucose tolerance influences the prognosis of hepatocellular carcinoma (HCC), but this mechanism is still not fully understood. We investigated the impact of the fasting serum levels of insulin and adiponectin on the prognosis of HCC and its recurrence. One hundred and forty patients with newly diagnosed HCC were enrolled in the prognosis study. Their fasting serum levels of insulin and adiponectin were determined. Of 140 patients, 59 patients who underwent curative treatment were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
2
10
1
1
Order By: Relevance
“…Moreover, serum RBP4, together with venous invasion and TNM stage, was identiWed as an independent risk factor of prognosis of patients with HCC. Opposite to our results, previous study suggested circulating insulin correlated with mortality in patients with colorectal cancer (Wolpin et al 2009) and HCC (Miuma et al 2009). The discrepancy may be attributed by the following reasons.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Moreover, serum RBP4, together with venous invasion and TNM stage, was identiWed as an independent risk factor of prognosis of patients with HCC. Opposite to our results, previous study suggested circulating insulin correlated with mortality in patients with colorectal cancer (Wolpin et al 2009) and HCC (Miuma et al 2009). The discrepancy may be attributed by the following reasons.…”
Section: Discussioncontrasting
confidence: 80%
“…The eVects of insulin are rather distinct between diVerent tumor types. The study of Miuma et al (2009) performed in early stage HCC and the liver disease background of patients with HCC was also diVerent from the patients recruited in our study. In summary, we suggest that serum RBP4, independent of serum insulin and IR, was a prognostic factor of HCC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In patients with HCV infection, HCC development is associated with increased fasting serum insulin level and by HOMA-IR [87] . Moreover, HCC recurrence has also been demonstrated to be related to HOMA-IR [88,89] . In addition, prognosis is worse in HCC patients with increased fasting serum insulin level or HOMA-IR [90] .…”
Section: Assessment Of Dm In Patients With Liver Diseasementioning
confidence: 99%
“…Hyperinsulinemia is an important pathophysiological factor and previous studies have reported that it was associated with cardiovascular disease (17) and hepatocellular carcinoma (HCC) (18). Moreover, our previous study showed that hyperinsulinemia affected the clinical course of early stage HCC (19).…”
Section: Discussionmentioning
confidence: 94%